Pengaruh Pemahaman Kitab Washoya Al Abaa' lil Abnaa' terhadap Akhlak Santri Pondok Pesantren Modern Al Hidayah Riau - Anggriawan, Ficho; Afriza, Afriza; Murhayati, Sri (Lembaga Yasin AlSys, 2025)
Morals are important to discuss because morals are the main pillar of human life. This study aim to assess the impact of comprehending the Book of Washoya Al Abaa’ lil Abnaa’ on the moral development of students at the Al Hidayah Modern Islamic Boarding School Riau. This research is quantitative associative, employing a proportionate stratified random sampling technique involving 232 students from the Al Hidayah Modern Islamic Boarding School Riau. This study employs sederhana regression analysis as its data analysis technique. The study's results indicate that the first hypothesis is supported, as the t-count value exceeds the t-table value (4.475 > 1.65145), and the significance value of the t-count is less than the alpha level set at 0.05 (0.000 < 0.05). It can be concluded that the null hypothesis (Ho) is rejected while the alternative hypothesis (Ha) is significantly accepted, indicating that comprehension of the Washoya Al Abaa' lil Abnaa' Book has a substantial impact on the morals of the students at Al Hidayah Riau Islamic Boarding School. The correlation coefficient between the variable of comprehension of the Washoya Al Abaa' lil Abnaa' Book (X1) and the morals variable (Y) is 0.409. This figure indicates a moderate correlation between the variable of comprehension of the Washoya Al Abaa' lil Abnaa' book (X1) and the morals variable (Y), as the computed r value is 0.409, which exceeds 0.05. The second hypothesis indicates that the calculated t value (-1.443) is less than the critical t value (1.65145), and the significance value of the calculated t (0.150) exceeds the alpha level of 0.05.